CRAN-09. CHOROID PLEXUS CARCINOMA IN INFANCY: FAVORABLE OUTCOME IN THREE PATIENTS TREATED WITH CHEMOTHERAPY. Issue 2 (22nd June 2018) - Antony, Reuben; Boggan, James; Ozturk, Arzu; Nicolaides, Theo; Jin, Lee-Way; Zwienenberg-Lee, Marike
Abstract: BACKGROUND: Children diagnosed with Choroid Plexus Carcinoma (CPC) in the first year of life usually have a very poor outcome partly because radiotherapy cannot be used as a part of treatment. We report 3 infants diagnosed with CPC in the first year of life including one patient who has Li-Fraumeni Syndrome who were successfully treated solely with chemotherapy. CASE REPORTS: Patient 1: diagnosed at age 1.5 months with a non-metastatic CPC in the 3rd ventricle. Following gross total tumor resection (GTR) he was treated on COG protocol POG 9923/34 using Vincristine, Etoposide, Cyclophosphamide and Cisplatin (VECC). He remains disease free 4 years post completion of therapy. Patient 2: diagnosed at age 8 months with a non-metastatic left lateral ventricle CPC. Following GTR he was treated on protocol POG 9932/34. He remains disease free 6 years post completion of therapy. Patient 3: Patient had a strong family history of cancer and was diagnosed with an adrenocortical neoplasm at birth. She was diagnosed at age 6 months with a right lateral ventricle CPC disseminated through the brainstem and spinal cord. After a GTR of the intracranial tumor she was treated as per the Head Start 2 (Regimen A) protocol using VECC and High Dose Methotrexate followed by triple autologous stem cell transplant (Carboplatin/Thiotepa conditioning). She remains disease free 8 months post completion of therapy. All patients experienced significant bacterial sepsis episodes, malnutrition and ototoxicity. CONCLUSION: Long term tumor control of CPC is possible using chemotherapy only protocols in very young infants.